Heat-conducting adhesive and preparation method thereof
By using fluorodiisocyanate, fluoropolymer, photoresponsive chain spreading agent and nanothermal filler in thermal adhesive, the problem of insufficient curing efficiency is solved, and a thermally conductive adhesive with high mechanical properties and photocontrollable bonding strength is achieved.
Patent Information
- Application Number
- CN202510270212.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-22
AI Technical Summary
Due to insufficient curing efficiency of existing thermal adhesives, the mechanical properties and bonding effect are reduced.
A thermally conductive adhesive is prepared by using a method of prepolymerization, including prepolymerization of fluorodiisocyanate and a polyol containing fluoro groups, adding a photoresponsive chain spreader and nanothermal thermal filler, and obtaining a thermally conductive adhesive with high curing efficiency and excellent mechanical properties through ultrasonic dispersion and moderate photocuring.
The curing efficiency of the thermally conductive adhesive is improved, its mechanical properties and bonding effect are enhanced, and through the introduction of the photoresponsive chain expander, the light-controllable adjustment of the bonding intensity is achieved.
Smart Images

Figure CN119859503A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane materials, and in particular relates to a thermally conductive adhesive and a preparation method thereof. Background Art
[0002] Electronic products (such as circuit boards, chips, displays, etc.) often need to protect their internal components from external environments (such as moisture, dust, corrosive gases, etc.) during use. Adhesives can effectively encapsulate electronic components, form a protective layer, and extend the service life of components. In electronic products, many components need to be fixed by bonding, especially for those miniature components that cannot be fixed by traditional methods (such as screws, clips, etc.). Adhesives can accurately locate and stabilize fixed components to ensure the reliability of products during long-term use. As electronic components (such as processors, graphics cards, LEDs, etc.) continue to be miniaturized and their functions continue to increase, the heat generated also increases accordingly. Thermally conductive fillers are usually added to adhesives for thermal management to help conduct heat and dissipate heat. This highly thermally conductive adhesive can effectively reduce the operating temperature of components and prevent failures caused by overheating.
[0003] In the related art, alumina fillers are added to epoxy resin or silicone rubber systems to achieve thermal conductivity and bonding effects. The addition of thermal conductive fillers, especially fillers with larger particle sizes, will occupy the original free volume in the resin or silicone rubber, affecting the movement of the resin or silicone rubber molecular chains, thereby reducing the efficiency of its curing reaction. Incomplete or uneven curing leads to a decrease in the mechanical properties and bonding effect of the adhesive. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a thermally conductive adhesive and a preparation method thereof, aiming to solve the problem that the mechanical properties and bonding effect of the adhesive are reduced due to insufficient curing efficiency.
[0005] In order to solve the above technical problems, the present invention is implemented as follows: a method for preparing a thermally conductive adhesive is provided, the steps comprising: S1, heating the fluorinated diisocyanate and the polyol containing a fluorinated group to 50-80° C. to carry out a prepolymerization reaction to obtain a fluorinated polyurethane prepolymer; S2, adding a photoresponsive chain extender to the polyurethane prepolymer, controlling the temperature to react within 60-80° C., and obtaining a polyurethane matrix with photoresponsive properties after the reaction is completed; S3, adding nano thermal conductive filler into the polyurethane matrix, adjusting the temperature to 25-30° C. for ultrasonic dispersion, and obtaining a thermal conductive adhesive.
[0006] In some embodiments of the present invention, in step S1, the fluorinated diisocyanate includes at least one of 4,4'-methylenebis(2-fluorophenyl isocyanate), 4,4'-methylenebis(3-fluorophenyl isocyanate), and 4,4'-methylenebis(2,3,5,6-tetrafluorophenyl isocyanate), and the polyol containing a fluorinated group includes at least one of 2,2,3,3-tetrafluoro-1,4-butanediol, a perfluoroalkyl-substituted polyether diol, and hexafluoroisopropanol-modified polycaprolactone diol.
[0007] In some embodiments of the present invention, the mass ratio of the fluorinated diisocyanate to the polyol containing a fluorinated group is 3-6:4-7.
[0008] In some embodiments of the present invention, step S1 comprises: S1.1. Place fluorinated diisocyanate and polyol containing fluorinated groups in a high temperature reaction kettle, raise the temperature to 50-80°C, introduce inert gas while stirring, the stirring speed is 300-500 rpm, and keep warm for 4-6 hours; S1.2, monitoring the concentration of isocyanate groups in the fluorinated diisocyanate by infrared spectroscopy or nitrogen-hydrogen analysis until a preset concentration is reached, stopping the introduction of the inert gas, and obtaining a fluorinated polyurethane prepolymer; S1.3, evacuate to -0.06~-0.09MPa, maintain stirring and heating temperature, detect the viscosity of the polyurethane prepolymer until it reaches the preset viscosity, and stop heating and stirring.
[0009] In some embodiments of the present invention, in step S2, the mass ratio of the polyurethane prepolymer to the photoresponsive chain extender is 8-9:1-2, and the photoresponsive chain extender includes at least one of coumarin-based diol, cinnamic acid-based diol, and azophenyl diamine.
[0010] In some embodiments of the present invention, step S2 comprises: S2.1, heating the fluoropolyurethane prepolymer to 50°C, introducing nitrogen while stirring, at a stirring speed of 100-300 rpm, and stirring for 20 min; S2.2, adding the photoresponsive chain extender dropwise to the fluoropolyurethane prepolymer until the addition is complete, heating to 60-80° C., and keeping the temperature for 2-3 hours to obtain a mixture; S2.3. Detect the concentration of isocyanate groups in the mixture until the concentration is 0, stop introducing the inert gas, and cool to room temperature to obtain a polyurethane matrix with light-responsive properties.
[0011] In some embodiments of the present invention, in step S3, the nano thermally conductive filler includes at least one of boron nitride nanosheets, carbon nanotubes, and aluminum oxide nanoparticles, and the mass ratio of the nano thermally conductive filler to the polyurethane matrix is 1-2:8-9.
[0012] In some embodiments of the present invention, step S3 includes: S3.1, placing the nano thermal conductive filler in a coupling agent for surface modification; S3.2. Add the surface-modified nano-thermal conductive filler to the polyurethane matrix, control the temperature at 25-30°C, perform ultrasonic dispersion for 15-30 minutes, and perform vacuum or static degassing to obtain a thermally conductive adhesive.
[0013] The present invention provides a thermally conductive adhesive, which is prepared by the above-mentioned method of preparing a thermally conductive adhesive, wherein the thermally conductive adhesive comprises a fluorinated diisocyanate, a polyol containing a fluorinated group, a photoresponsive chain extender and a nano thermally conductive filler; wherein: The fluorinated diisocyanate is used to provide a hard segment of the polyurethane skeleton and enhance the chemical stability of the thermally conductive adhesive; The polyol containing fluorinated groups is used to provide a polyurethane skeleton soft segment to improve the surface properties of the thermally conductive adhesive; The photoresponsive chain extender is used to introduce a light-triggered reversible cross-linking function to achieve light-controllable adjustment of the bonding strength of the thermally conductive adhesive; Compared with the prior art, the thermally conductive adhesive and the preparation method thereof in the present invention have the following beneficial effects: The introduction of photoresponsive chain extenders enables the polyurethane network to produce additional or faster crosslinking reactions under UV or appropriate wavelength light. A high degree of crosslinking can be achieved under relatively mild temperature conditions, which helps to shorten the curing time required for thermal conductive adhesives and improve curing efficiency. With the help of light, chain extension reactions can be quickly activated when needed or bonding within the system can be promoted, reducing the slow curing at low temperatures like ordinary adhesives.
[0014] The fluorinated diisocyanate and fluorinated polyol used give the polyurethane structure the advantages of low surface energy, chemical resistance and weather resistance. In high temperature, high humidity or corrosive environments, it can maintain good adhesion and mechanical performance of thermally conductive adhesives, and significantly improve the tensile strength, shear strength and peel strength of thermally conductive adhesives. In the low surface energy environment of the fluorinated polyurethane system, combined with ultrasonic dispersion and moderate light curing, it is easy to obtain a relatively uniform distribution of nano-thermal conductive fillers on a microscopic scale. Nano-thermal conductive fillers are evenly distributed in thermally conductive adhesives to avoid concentrated stress areas, reduce microcracks or local peeling problems, and have better overall mechanical properties and bonding reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The figure is a schematic flow chart of a method for preparing a thermally conductive adhesive in one embodiment of the present invention. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0017] Please refer to Figure 1 The present invention provides a method for preparing a thermally conductive adhesive, the steps comprising: S1. Heat the fluorinated diisocyanate and the polyol containing a fluorinated group to 50-80° C. to carry out a prepolymerization reaction to obtain a fluorinated polyurethane prepolymer.
[0018] In step S1, the fluorinated diisocyanate includes at least one of 4,4'-methylenebis(2-fluorophenyl isocyanate), 4,4'-methylenebis(3-fluorophenyl isocyanate), and 4,4'-methylenebis(2,3,5,6-tetrafluorophenyl isocyanate), and the polyol containing a fluorinated group includes at least one of 2,2,3,3-tetrafluoro-1,4-butanediol, perfluoroalkyl substituted polyether diol, and hexafluoroisopropanol modified polycaprolactone diol. The mass ratio of the fluorinated diisocyanate to the polyol containing a fluorinated group is 3-6:4-7.
[0019] Step S1 includes: S1.1. Place fluorinated diisocyanate and polyol containing fluorinated groups in a high-temperature reaction kettle, raise the temperature to 50-80°C, introduce inert gas while stirring, the stirring speed is 300-500 rpm, and keep warm for 4-6 hours.
[0020] By introducing inert gas (such as nitrogen or argon), moisture and oxygen in the air can be effectively removed, side reactions (such as urea formation, condensation, etc.) between isocyanate groups (NCO) and water or oxygen can be avoided, and the efficiency and product purity of the prepolymerization reaction can be improved. Controlling the system temperature at 50~80℃ can not only ensure the smooth addition reaction between isocyanate and polyol, but also avoid decomposition or side reactions caused by excessive temperature. A stirring speed of 300~500rpm can make the fluorodiisocyanate and polyol contact evenly, reduce the phenomenon of insufficient or excessive local reaction, and obtain a stable and controllable prepolymer molecular weight. Keeping warm at this temperature and stirring intensity for 4~6h can allow most isocyanate groups (NCO) and alcohol groups (OH) to react evenly and fully, improving the synthesis efficiency and stability of polyurethane prepolymers. Under relatively mild and uniform reaction conditions, side reactions are minimized and the reaction conversion rate is improved, laying the foundation for subsequent precise control of the NCO content and viscosity of the prepolymer. Inert gas protection can significantly reduce the probability of side reactions such as hydrolysis or oxidation, and improve product purity and performance consistency.
[0021] S1.2. Monitor the concentration of isocyanate groups in the fluorinated diisocyanate by infrared spectroscopy or nitrogen-hydrogen analysis until a preset concentration is reached, stop introducing the inert gas, and obtain a fluorinated polyurethane prepolymer.
[0022] Tracking the extent of NCO group consumption using infrared spectroscopy (FTIR) or nitrogen-hydrogen analysis (such as NCO content titration or NMR) allows researchers / producers to understand the concentration of remaining isocyanate in the system during the reaction and accurately control the reaction endpoint.
[0023] Once the monitoring shows that the NCO group concentration reaches the target value (preset concentration), the inert gas is immediately stopped and the next step can be carried out to avoid overreaction or continued side reactions (such as excessive crosslinking and molecular weight loss). The chemical structure of the prepolymer is precisely controlled to ensure that the final polyurethane prepolymer has a predictable NCO content and molecular weight distribution.
[0024] Infrared spectroscopy is used to detect the concentration change of isocyanate groups (NCO) in polyurethane prepolymers, thereby determining the extent of the reaction. The instrument is a Fourier transform infrared spectrometer (FTIR).
[0025] Take a small amount of polyurethane prepolymer sample from the reactor, place it in the sample cell of the infrared spectrum, turn on the FTIR device, and set appropriate scanning parameters (scanning range: 4000cm -1 ~400cm -1 , the number of scans is 16~32 times). Set the resolution to 4cm -1 , which helps to accurately analyze the characteristic absorption peaks of the NCO group.
[0026] Start scanning and record the infrared spectrum transmitted from the sample. Observe 2270cm -1 The absorption peak near is the characteristic absorption peak of the isocyanate group (NCO). The changes of this peak are monitored by comparing the spectral data before and after the reaction. When the absorption intensity of this peak decreases to the set threshold, it means that the concentration of the isocyanate group has reached the predetermined requirement and the reaction is close to completion. Through baseline correction, the reduction of the NCO group is quantitatively analyzed. The conversion rate of the reaction can be obtained by calculating the absorbance change of the NCO peak, and it can be used to determine when to stop the reaction.
[0027] Nitrogen hydrogen analysis (NCO content determination) uses a nitrogen hydrogen analyzer. This method is suitable for directly measuring the isocyanate group content in the reaction with high accuracy.
[0028] Take an appropriate amount of polyurethane prepolymer sample and weigh it. Place the sample in the sample tube of the nitrogen hydrogen analyzer. Set the appropriate temperature (200~300℃) and atmosphere (use nitrogen or helium as carrier gas) of the nitrogen hydrogen analyzer. Set the analysis time to 2~5 minutes. The isocyanate groups (NCO) in the sample are converted to amino groups (NH 2 ) or nitrogen and hydrogen, and cooperate with the gas detection system to measure the amount of nitrogen and hydrogen gas released during the reaction.
[0029] The concentration of NCO groups is calculated based on the amount of nitrogen and hydrogen gas released to determine whether the reaction is complete. When the concentration of NCO groups reaches the set value, the reaction is stopped.
[0030] In the above detection process, the preset concentration of isocyanate groups is 1%~5%.
[0031] S1.3, evacuate to -0.06~-0.09MPa, maintain stirring and heating temperature, test the viscosity of polyurethane prepolymer until it reaches the preset viscosity, stop heating and stirring. The preset viscosity is 50~3000Pa·s.
[0032] By vacuuming, volatile solvents, excess monomers or other by-products that may remain during the reaction can be removed, further improving the purity of the prepolymer. Avoid residual solvents or unreacted monomers in the final product from having adverse effects on subsequent processes and performance (such as bubbles, odor, deterioration of mechanical properties, etc.). Under the conditions of maintaining certain stirring and heating, online detection of prepolymer viscosity allows the operator to determine whether the system fluidity or molecular weight meets the set standards. The preset viscosity often corresponds to a specific molecular weight range and flow characteristics suitable for subsequent processing or coating processes. When the viscosity reaches the target value, heating and stirring are stopped to avoid further polymerization or side reactions that lead to viscosity loss, thereby improving the operability of the finished product in subsequent application scenarios. Through decompression and viscosity regulation, precise control of the molecular weight, purity and fluidity of the prepolymer is achieved; the concerns about residual solvents and side reactions in subsequent process links are reduced, and the consistency and processability of the finished product are improved.
[0033] S2, adding a photoresponsive chain extender to a polyurethane prepolymer, controlling the temperature to react within 60-80°C, and obtaining a polyurethane matrix having photoresponsive properties after the reaction is completed. In step S2, the mass ratio of the polyurethane prepolymer to the photoresponsive chain extender is 8-9:1-2, and the photoresponsive chain extender includes at least one of coumarin-based diol, cinnamic acid-based diol, and azophenyl diamine.
[0034] Step S2 includes: S2.1. Heat the fluoropolyurethane prepolymer to 50°C, introduce nitrogen while stirring at a speed of 100-300 rpm for 20 min.
[0035] Maintaining stirring at 50°C can make the fluoropolyurethane prepolymer fully melt or flow evenly, which is conducive to the subsequent addition and dispersion of the photoresponsive chain extender. At the same time, it can help eliminate the trace moisture or low-boiling impurities that may exist in the system (gradually escape under the protection of nitrogen) and reduce side reactions (such as the reaction of NCO with water to form urea groups). The introduction of nitrogen can avoid the interference of air and moisture on the remaining NCO groups or side reactions such as oxidation, improve the purity of the reaction, and ensure the smooth progress of the subsequent chain extension reaction. Setting the temperature at 50°C and maintaining stirring can ensure that the prepolymer flows at a lower viscosity and promote the uniformity of the system. Stirring at 100~300rpm helps to evenly distribute the temperature and components in the system, and fully prepares for the addition of the photoresponsive chain extender in the next step. Unifying the temperature field and removing impurities creates a uniform and stable reaction environment for the subsequent addition of the photoresponsive chain extender; reducing the probability of NCO groups contacting water or oxygen, reducing by-products, and ensuring the stability of the performance of the final photoresponsive polyurethane.
[0036] S2.2. Add the photoresponsive chain extender dropwise into the fluoropolyurethane prepolymer until the addition is complete, raise the temperature to 60-80°C, and keep the temperature for 2-3 hours to obtain a mixture.
[0037] Slowly adding the photoresponsive chain extender (such as coumarin-based diol, cinnamic acid-based diol, azophenyl diamine) to the prepolymer can prevent the chain extender from being too concentrated in a local area, resulting in a too fast instantaneous reaction or microgel phenomenon, and ensure that the system reacts evenly and smoothly. At higher temperatures (60-80°C), the NCO group and the -OH / -NH 2 The reaction rate is increased, accelerating chain growth and structural regulation. Keeping warm for 2 to 3 hours allows the photoresponsive chain extender to fully react with the NCO group of the prepolymer and insert the photoresponsive group into the main chain or side chain of the molecule. With the reaction of the chain extender, the molecular weight and degree of cross-linking of the polyurethane increase moderately, giving the polyurethane matrix properties such as light-induced reversible cross-linking / decross-linking or cis-trans isomerization. Different photoresponsive groups (coumarin, cinnamic acid, azobenzene) bring different sensitive bands and reversible mechanisms to meet the needs of diverse applications. The dripping and heating methods ensure that the reaction is sufficient without getting out of control, and a photoresponsive polyurethane matrix with predictable molecular structure is obtained; through long-term constant temperature reaction, the photoresponsive groups are distributed in the polyurethane structure, giving the material innovative functions such as photoreversible adhesion and optical regulation.
[0038] That is, when the photoresponsive chain extender is a coumarin-based diol or a cinnamic acid-based diol, the structure changes after being exposed to light, and a cyclization reaction or photoinduced crosslinking occurs. These reactions can increase the degree of crosslinking between polyurethane molecules, thereby improving the strength, toughness and durability of the adhesive layer. Through this photoresponsive reaction, the molecular network of the adhesive is more compact, improving its stability under heat, humidity and other conditions, and enhancing the adhesion to the substrate.
[0039] Coumarin-based diols are very sensitive to UV light. Their cyclization reaction requires UV light with a wavelength of 340-370nm. The typical absorption peak of the coumarin group is between 330nm and 370nm. The cyclization reaction of coumarin-based diols requires high-intensity light, which is generally between 20-50mW / cm². Under strong UV light, the reaction speed is faster, so the photoresponsiveness in coatings or adhesives can be more significantly manifested. After illumination, the coumarin group undergoes a photocyclization reaction to form a structure with cross-linking characteristics, thereby increasing the cross-linking density and strength of the polyurethane matrix.
[0040] The photoresponse characteristics of cinnamic acid diol are sensitive to ultraviolet light, especially light with a wavelength between 320-370nm. Its photoresponse mechanism mainly involves photoinduced crosslinking or photoinduced polymerization, and the absorption wavelength range is also similar to coumarin. The crosslinking reaction of cinnamic acid diol also requires ultraviolet light irradiation of a certain intensity. Light intensity in the range of 30-60mW / cm² can activate the crosslinking reaction. Especially in application scenarios that require a stronger degree of crosslinking, increasing the light intensity can increase the crosslinking density. Under ultraviolet light irradiation, cinnamic acid diol undergoes a photoinduced crosslinking reaction, increasing the crosslinking degree of polyurethane, and improving the strength, toughness and durability of the adhesive layer.
[0041] When the photoresponsive chain extender is azophenyldiamine, cis-trans isomerization or photodimerization reaction can be achieved under light. These reactions can control the bonding strength, so that the bonding performance changes reversibly under light and no light conditions. This adjustable bonding performance can be adjusted according to actual needs and is suitable for application scenarios that require photosensitivity or response. After the thermal conductive adhesive is applied to the location where bonding is required, the viscosity is reduced by increasing the light intensity.
[0042] Azophenyl diamine is highly responsive to UV light, especially in the wavelength range of 350-450nm, showing strong light absorption. The typical absorption peak of the azophenyl group is between 360nm and 430nm. The reaction of azophenyl diamine requires moderate light intensity, and light intensity between 10-30mW / cm² can effectively activate cis-trans isomerization or photodimerization reaction. Higher intensity light helps to accelerate the reaction rate and adjust the bonding strength of polyurethane.
[0043] S2.3. Detect the concentration of isocyanate groups in the mixture until the concentration is 0, stop introducing the inert gas, and cool to room temperature to obtain a polyurethane matrix with light-responsive properties.
[0044] Use infrared spectroscopy (FTIR) or nitrogen-hydrogen analysis to observe the changes in the NCO peak. When its concentration drops to 0 or close to 0 (within the threshold range), it means that most of the NCO groups have fully reacted with the chain extender. Stop the inert gas and heating in time to prevent continued reaction or side reactions from causing excessive molecular weight / gelation. If there are still unreacted NCO groups remaining in the system, it will affect the later performance of the material (viscosity loss, unstable mechanical properties, etc.), or react with moisture to generate by-products during storage / use. Stop the reaction when the NCO group content reaches the set threshold, and the product molecular weight and light response characteristics can be accurately controlled. During the room temperature cooling process, the molecular structure is basically fixed, and a polyurethane matrix with both fluorinated characteristics and light response properties is generated. Stopping the inert gas protection means that the reaction is complete and the material can be transferred to subsequent processes (such as thermal conductive filler dispersion, degassing, molding, etc.). Completely consume the NCO group to obtain a stable terminal polyurethane structure; ensure that the photoresponsive group reacts completely with the NCO group to improve the consistency and controllability of the finished product's reversible bonding, optical regulation and other functions; maintain a suitable molecular weight and fluidity for subsequent processing, storage and application.
[0045] S3, adding nano thermal conductive filler into the polyurethane matrix, adjusting the temperature to 25-30°C for ultrasonic dispersion, and obtaining a thermal conductive adhesive. In step S3, the nano thermal conductive filler includes at least one of boron nitride nanosheets, carbon nanotubes, and aluminum oxide nanoparticles, and the mass ratio of the nano thermal conductive filler to the polyurethane matrix is 1-2:8-9.
[0046] Step S3 includes: S3.1, placing the nano thermal conductive filler in a coupling agent for surface modification. The coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-chloropropyltriethoxysilane, γ-epoxypropyltriethoxysilane, alcohol coupling agent, titanane coupling agent, and fluorinated coupling agent.
[0047] Silane coupling agent improves the interface between filler and polyurethane matrix through chemical bonding, and enhances the dispersion of filler in the matrix. Through surface modification, the dispersion of filler is more uniform, and the aggregation phenomenon between fillers is reduced, thereby improving the thermal conductivity. The filler after surface modification is easier to be evenly distributed, avoiding agglomeration, and improving the mechanical properties of the composite material.
[0048] The alcohol-based coupling agent contains an alcohol group with hydrogen bonding activity, which can form hydrogen bonds with the filler surface. Isopropyl alcohol or ethanol enhances the affinity of the filler to the polyurethane matrix through surface modification. The alcohol-based coupling agent can effectively improve the dispersibility of the filler through hydrogen bonding and avoid its agglomeration in the polyurethane matrix. The coupling agent can enhance the interface bonding between the filler and the polyurethane matrix and optimize the thermal conductivity path of the composite material through the change of surface affinity.
[0049] The titanane coupling agent contains a titanyl group and an organic group, which can react with the filler surface and the hydroxyl group in the polyurethane matrix through the bonding action of titanium oxide. Isopropyl tri(dimethylamino)titanium, a titanane coupling agent with an amino group, can react with the isocyanate group or hydroxyl group in the polyurethane through the amino group to enhance the bonding force between the filler and the matrix. The titanyl group of the titanane coupling agent can react with the hydroxyl group on the filler surface or in the polyurethane matrix to further enhance the bonding force between the filler and the matrix and improve the mechanical and thermal conductivity of the composite material. The use of the titanane coupling agent can also enhance the thermal stability of the composite material, especially in high-temperature applications.
[0050] Fluorinated coupling agents contain fluorinated groups, which can enhance the hydrophobicity of fillers and improve the corrosion resistance of materials in specific environments. For example, trifluorochlorosilane can react with the surface of fillers to improve the hydrophobicity of fillers and substrates and increase the water resistance of materials. Fluorinated coupling agents can significantly improve the hydrophobicity of the filler surface by introducing fluorine elements, making the filler less susceptible to moisture in environments with high moisture content and adapting to more working environments. The application of this coupling agent improves the anti-pollution property of fillers in polyurethane matrix and avoids insufficient surface hydrophilicity or interference from pollutants.
[0051] Surface modification can significantly improve the interfacial compatibility between nano-thermal conductive fillers and polyurethane matrix by introducing coupling agents. The surface of the filler carries active groups that can react with the OH group or NCO group of the polyurethane matrix to form chemical bonds, thereby improving the dispersibility and stability of the filler. For example, the surface of boron nitride nanosheets and carbon nanotubes is polar or hydrophilic. Through modification with coupling agents (such as silane coupling agents, titanane coupling agents, etc.), the surface can be made more oleophilic or hydrophobic, thereby optimizing the interfacial interaction with polyurethane. Through surface modification, the filler can be more evenly dispersed in the polyurethane matrix. Especially for nanofillers, surface modification can reduce the agglomeration phenomenon between particles and improve the thermal conductivity of the material. The modified filler can form a more stable dispersion in the polyurethane matrix, avoiding the decrease in thermal conductivity due to agglomeration. The use of coupling agents can effectively improve the adhesion between the filler and the matrix, thereby improving the mechanical properties of the composite material, increasing its durability, and preventing the filler from falling off due to external forces during use. Certain coupling agents (such as fluorinated coupling agents) not only improve the bonding strength between fillers and substrates, but also give materials additional hydrophobicity, anti-pollution or high temperature resistance, thus expanding the application scope of composite materials.
[0052] S3.2. Add the surface-modified nano-thermal conductive filler into the polyurethane matrix, control the temperature at 25-30°C, perform ultrasonic dispersion for 15-30 minutes, and perform vacuum or static degassing to obtain a thermally conductive adhesive.
[0053] Ultrasonic dispersion is to disperse the nano-thermal conductive filler evenly in the polyurethane matrix through the high-frequency oscillation of ultrasound. The high energy of ultrasound can break up the agglomerated nanoparticles, prevent them from forming large particle clumps in the matrix, and ensure the uniform distribution of the filler in the matrix. This is crucial to improving the thermal conductivity and mechanical properties of the material. The uniform dispersion of the nano-thermal conductive filler in the polyurethane matrix helps to form a continuous heat conduction channel and significantly improve the thermal conductivity of the composite material. Through ultrasonic dispersion, the nanoparticles can be arranged along the direction of heat flow, optimize the thermal conductive network structure of the composite material, and thus improve the thermal conductivity of the material. Ultrasonic dispersion helps to maintain the stable dispersion state of the nano-filler and avoid stratification or precipitation of the filler during long-term use. Good dispersion not only improves the thermal conductivity, but also enhances the mechanical properties of the composite material, such as tensile strength and hardness. Ultrasonic dispersion at a lower temperature can ensure that the polyurethane matrix is not affected by excessive temperature, avoid premature cross-linking or curing, maintain good fluidity and processing performance, and facilitate subsequent processing operations such as molding or coating. By being evenly dispersed, nanofillers can evenly transfer external heat and further enhance the heat dissipation capacity of the material. They are especially suitable for application scenarios that require efficient heat dissipation, such as heat dissipation of electronic equipment, high-power LEDs, and automotive parts.
[0054] In one embodiment, before step S3.2, step S3.1.1 is also included; S3.1.1. Add thermal crosslinking units to the mixture of nano-thermal conductive filler and polyurethane matrix, heat to its decomposition temperature (such as 60-80°C or 100-130°C, depending on the specific compound) to trigger crosslinking; maintain at the heating temperature for 30-60 minutes to evenly complete crosslinking or phase change dispersion. During the heating and insulation stage, use mechanical stirring at 50-200 rpm to prevent local overheating and ensure that the material is evenly distributed during the heating process.
[0055] The crosslinking degree of the heat-crosslinking unit is substantially fixed after cooling, wherein the heat-crosslinking unit comprises at least one of azobisisobutyronitrile, di(tert-butylperoxy)dicarbonyl, and bismaleimide.
[0056] Azobisisobutyronitrile decomposes at about 60~80℃, releasing free radicals, initiating polymerization or cross-linking reactions. It is often used in thermosetting resins and polymer free radical polymerization. It improves cross-linking density and heat resistance in polyurethane or other elastomer systems.
[0057] Di(tert-butylperoxy)dicarbonyl decomposes at higher temperatures (such as 130~180℃) to generate free radicals, which react with the polymer main chain or cross-linking points to form a thermosetting network, thereby increasing the mechanical strength and stability of the thermally conductive adhesive at high temperatures.
[0058] Under heating conditions, the maleimide group of bismaleimide can undergo high-temperature cross-linking reaction with diene or other groups to form a stable network structure with high heat resistance, thereby improving the temperature resistance and bonding ability of the thermal conductive adhesive.
[0059] The viscosity of the prepared thermally conductive adhesive is controlled between 1000 and 30000 cP to meet the dispensing and bonding requirements of electronic products.
[0060] Fine tuning of the viscosity of the thermally conductive adhesive can be achieved through the control equation; in, is the overall viscosity of the thermally conductive adhesive, is the viscosity without adding nano thermal conductive filler, is the volume fraction of nano thermal conductive filler, , is the volume of the nano thermal conductive filler, is the overall volume of the thermally conductive adhesive, is the maximum volume fraction that the nano thermally conductive filler can achieve in the thermally conductive adhesive, is the shape factor of the nano thermal conductive filler.
[0061] At lower nano-thermal conductive filler concentrations, [η] can be inferred by fitting the viscosity versus φ curve. If the viscosity curve rises linearly at very low concentrations, then η≈ (1+[η]ϕ), to obtain [η]. The viscosity η is measured at a series of different nano-thermal conductive filler volume fractions ϕ, and multi-point regression is performed to obtain the corresponding optimal value. Spherical or nearly spherical fillers: [η]≈2.5~3, flake fillers: [η]≈5~10.
[0062] If the overall viscosity of the thermally conductive adhesive If the viscosity is too low, the viscosity can be increased by increasing the amount of nano-thermal conductive filler. If the viscosity is too high, the viscosity can be reduced by adding a regulating solvent. The regulating solvent includes at least one of acetone, butanone, tetrahydrofuran, N,N-dimethylformamide, N-methylpyrrolidone, and ethyl acetate. Increasing the regulating solvent can mainly expand the total volume, thereby reducing the volume fraction φ of the nano-thermal conductive filler, thereby diluting the viscosity.
[0063] In applications such as electronic products, thermally conductive adhesives often require automatic dispensing machines or screen printers to apply adhesives. If the viscosity is too high, the thrust requirements of the dispensing equipment will increase, and it is easy to cause wire drawing and adhesive breakage; if the viscosity is too low, it is easy to flow, which is not conducive to precise positioning and maintaining shape.
[0064] By controlling the viscosity within a suitable range (such as 5000 ~ 8000 cP, 8000 ~ 12000 cP, 12000 ~ 20000 cP), the thermal conductive adhesive can be smoothly extruded and evenly coated, reducing defects caused by equipment blockage or uneven coating. When the viscosity is moderate, the thermal conductive adhesive is easier to exhaust or degas during stirring, dispersing or gluing. Too high a viscosity will retain bubbles, affecting heat dissipation and mechanical properties; too low a viscosity will easily cause sagging and fail to firmly cover the surface of the substrate. The appropriate viscosity is convenient for ultrasonic or vacuum degassing, and ensures the formation of a uniform and dense bonding layer after gluing.
[0065] The present invention provides a thermally conductive adhesive, which is prepared by a method for preparing the thermally conductive adhesive. The thermally conductive adhesive includes a fluorinated diisocyanate, a polyol containing a fluorinated group, a photoresponsive chain extender, and a nano thermally conductive filler; wherein: Fluorinated diisocyanate is used to provide a hard segment in the polyurethane skeleton and enhance the chemical stability of the thermally conductive adhesive; Polyols containing fluorinated groups are used to provide soft segments in the polyurethane skeleton and improve the surface properties of thermally conductive adhesives; Photoresponsive chain extenders are used to introduce light-triggered reversible cross-linking functionality to achieve light-controllable regulation of the bonding strength of thermally conductive adhesives; Nano thermally conductive fillers are used to improve the thermal conductivity of thermally conductive adhesives.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a thermally conductive adhesive, characterized in that the steps include: S1, heating the fluorinated diisocyanate and the polyol containing a fluorinated group to 50-80° C. to carry out a prepolymerization reaction to obtain a fluorinated polyurethane prepolymer; S2, adding a photoresponsive chain extender to the polyurethane prepolymer, controlling the temperature to react within 60-80° C., and obtaining a polyurethane matrix with photoresponsive properties after the reaction is completed; S3, adding nano thermal conductive filler into the polyurethane matrix, adjusting the temperature to 25-30° C. for ultrasonic dispersion, and obtaining a thermal conductive adhesive.
2. The method for preparing a thermally conductive adhesive according to claim 1, characterized in that: In step S1, the fluorinated diisocyanate includes at least one of 4,4'-methylenebis(2-fluorophenyl isocyanate), 4,4'-methylenebis(3-fluorophenyl isocyanate), and 4,4'-methylenebis(2,3,5,6-tetrafluorophenyl isocyanate), and the polyol containing a fluorinated group includes at least one of 2,2,3,3-tetrafluoro-1,4-butanediol, a perfluoroalkyl-substituted polyether diol, and hexafluoroisopropanol-modified polycaprolactone diol.
3. A method for preparing a thermally conductive adhesive according to claim 1 or 2, characterized in that: The mass ratio of the fluorinated diisocyanate to the polyol containing a fluorinated group is 3-6:4-7.
4. The method for preparing a thermally conductive adhesive according to claim 1, characterized in that: Step S1 includes: S1.
1. Place fluorinated diisocyanate and polyol containing fluorinated groups in a high temperature reaction kettle, raise the temperature to 50-80°C, introduce inert gas while stirring, the stirring speed is 300-500 rpm, and keep warm for 4-6 hours; S1.2, monitoring the concentration of isocyanate groups in the fluorinated diisocyanate by infrared spectroscopy or nitrogen-hydrogen analysis until a preset concentration is reached, stopping the introduction of the inert gas, and obtaining a fluorinated polyurethane prepolymer; S1.3, evacuate to -0.06~-0.09MPa, maintain stirring and heating temperature, detect the viscosity of the polyurethane prepolymer until it reaches the preset viscosity, and stop heating and stirring.
5. The method for preparing a thermally conductive adhesive according to claim 1, characterized in that: In step S2, the mass ratio of the polyurethane prepolymer to the photoresponsive chain extender is 8-9:1-2, and the photoresponsive chain extender includes at least one of coumarin-based diol, cinnamic acid-based diol, and azophenyl diamine.
6. The method for preparing a thermally conductive adhesive according to claim 1, characterized in that: Step S2 includes: S2.1, heating the fluoropolyurethane prepolymer to 50°C, introducing nitrogen while stirring, at a stirring speed of 100-300 rpm, and stirring for 20 min; S2.2, adding the photoresponsive chain extender dropwise to the fluoropolyurethane prepolymer until the addition is complete, heating to 60-80° C., and keeping the temperature for 2-3 hours to obtain a mixture; S2.
3. Detect the concentration of isocyanate groups in the mixture until the concentration is 0, stop introducing the inert gas, and cool to room temperature to obtain a polyurethane matrix with light-responsive properties.
7. The method for preparing a thermally conductive adhesive according to claim 1, characterized in that: In step S3, the nano thermally conductive filler includes at least one of boron nitride nanosheets, carbon nanotubes, and aluminum oxide nanoparticles, and the mass ratio of the nano thermally conductive filler to the polyurethane matrix is 1-2:8-9.
8. The method for preparing a thermally conductive adhesive according to claim 7, characterized in that: Step S3 includes: S3.1, placing the nano thermal conductive filler in a coupling agent for surface modification; S3.
2. Add the surface-modified nano-thermal conductive filler to the polyurethane matrix, control the temperature at 25-30°C, perform ultrasonic dispersion for 15-30 minutes, and perform vacuum or static degassing to obtain a thermally conductive adhesive.
9. A thermally conductive adhesive, characterized in that: A method for preparing a thermally conductive adhesive according to any one of claims 1 to 8, wherein the thermally conductive adhesive comprises a fluorinated diisocyanate, a polyol containing a fluorinated group, a photoresponsive chain extender, and a nano-thermal conductive filler; wherein: The fluorinated diisocyanate is used to provide a hard segment of the polyurethane skeleton and enhance the chemical stability of the thermally conductive adhesive; The polyol containing fluorinated groups is used to provide a polyurethane skeleton soft segment to improve the surface properties of the thermally conductive adhesive; The photoresponsive chain extender is used to introduce a light-triggered reversible cross-linking function to achieve light-controllable adjustment of the bonding strength of the thermally conductive adhesive; The nano thermally conductive filler is used to improve the thermal conductivity of the thermally conductive adhesive.